Comparative Study of Ten Bacteriocins of Clostridium perfringens - Mahony, D. E. (1978)
Bacteriocins of Clostridium perfringens were prepared by ammonium sulfate precipitation of supernatant broth from 10 bacteriocinogenic strains. These bacteriocins were compared with respect to their ability to produce spheroplasts in a sensitive indicator strain; their inducibility; sensitivity to pH, proteolytic enzymes, and boiling; and their effect on macromolecular synthesis. Two bacteriocins were stable over a wide range of pH values and resisted boiling, and three bacteriocins were resistant to trypsin. Five bacteriocins shut down DNA, RNA, and protein synthesis; three bacteriocins had varying effects on DNA and RNA synthesis; and two bacteriocins had little effect on macromolecular synthesis. Antiserum prepared against one bacteriocin highly neutralized three bacteriocins with partial neutralization of five others; two bacteriocins were unaffected. Mutant strains selected for resistance to bacteriocin 28 also demonstrated coresistance to two other closely related bacteriocins and partial resistance to five others.